Adipose Tissue Grafting Improves Contour Deformities Related Hyperpigmentation of Face. Issue 5 (July 2020) - Bashir, Afzaal; Bashir, Muhammad Mustehsan; Sohail, Muhammad; Choudhery, Mahmood S.
Abstract : Abstract: Contour deformities of face are commonly associated with overlying skin hyperpigmentation. Such hyperpigmentation causes aesthetic problems as well as makes contour deformities more prominent. Conventional surgical and cosmetic approaches to treat hyperpigmentation have limitations and therefore it is imperative to use other innovative techniques to simultaneously heal the contour deformity and also to remove hyperpigmentation. The current study aims to evaluate the effect of autologous adipose tissue in improving contour deformities related hyperpigmentation of face. One hundred patients with contour deformities related hyper-pigmentation of overlying skin were enrolled from February 2017 to January 2018. Adipose tissue was harvested from each patient and processed under sterilized conditions. Purified fat collected in a 10cc Luer-Lok syringe was transferred to 1cc syringes and injected into affected areas of face. The patients were followed for 12 months after adipose tissue injections. Both subjective and objective assessment was performed before treatment and 12 months after adipose tissue injections. Results indicated that after adipose tissue grafting, there was a statistically significant improvement in hyperpigmentation of skin. Most of the patients were highly satisfied after use of adipose tissue injections. Image J scanning also showed significant changes in hyperpigmentation of face after adipose tissue use. In all parameters, the patient exhibited statistically significant improvement. In conclusion, autologous fat grafting is a promising and effective therapeutic approach for hyperpigmentation associated with contour deformities of face. Abstract : Supplemental Digital Content is available in the text